2020
DOI: 10.1371/journal.pone.0232543
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of phenotypic pyrazinamide resistance and its association with pncA gene mutations in Mycobacterium tuberculosis isolates from Uganda

Abstract: There is a high prevalence of phenotypic PZA resistance among TB patients in Uganda. The low sensitivity of pncA gene sequencing confirms the already documented discordances suggesting other mechanisms of PZA resistance in Mycobacterium tuberculosis.data collection and analysis, decision to publish, or preparation of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…PZA was always controversial in the treatment of MDR-TB and XDR-TB, some studies showed that PZA resistant or not did not impact its anti-microbial activity (21,26,27), however, the high resistant rate of PZA had been considered its application in the future (28). In the present study, we tested PZA resistance by MIC value, the resistance rate was 50.9%.…”
Section: Discussionmentioning
confidence: 82%
“…PZA was always controversial in the treatment of MDR-TB and XDR-TB, some studies showed that PZA resistant or not did not impact its anti-microbial activity (21,26,27), however, the high resistant rate of PZA had been considered its application in the future (28). In the present study, we tested PZA resistance by MIC value, the resistance rate was 50.9%.…”
Section: Discussionmentioning
confidence: 82%
“…However, Allana et al [ 52 ] reported that 70% of multidrug-resistant and 96% of extensively drug-resistant M. tuberculosis isolates in South Africa and Georgia were positive for the pncA gene. Detection of this gene in clinical M. tuberculosis isolates has been published from other countries, such as Pakistan [ 53 ] and Uganda [ 54 ]. The data obtained in our study, therefore, show that the environmental abundance of this gene could be driven by bacteria carrying this resistance gene in the wastewater environment or a prevalence within the local population/communities.…”
Section: Discussionmentioning
confidence: 99%
“…The review further demonstrated that a great number of infectious diseases have been shown to resist available and routine therapy in the Ugandan context, for example, tuberculosis [19][20][21], pneumonia [22,23], salmonellosis [24,25], malaria [26,27], gonorrhea [28][29][30] and other urinary tract infections and respiratory infections, as well as important viral and fungal infections. There has been detection of wide spread beta lactam and non-beta lactam antibiotic resistance reported in district referral hospitals [31] as well as multidrug resistance amongst clinical isolates [32,33].…”
Section: Discussionmentioning
confidence: 99%